Miraculous mysteries : locked room mysteries and impossible crimes - Edwards, Martin, 1955- (British Library crime classics., 2017)
Impossible crime stories have been relished by puzzle-lovers ever since the invention of detective fiction. Fiendishly intricate cases were particularly well suited to the cerebral type of detective story that became so popular during the golden age of murder, between the two world wars. But the tradition goes back to the days of Edgar Allan Poe and Wilkie Collins, and impossible crime stories have been written by such luminaries as Arthur Conan Doyle, G.K. Chesterton, Dorothy L. Sayers and Margery Allingham. This anthology celebrates their work, alongside long-hidden gems by less familiar writers. Together these stories demonstrate the range and high accomplishment of the classic British impossible crime story over more than half a century.